Handel's realm in music - Culp, Amanda (My University, 1900)
Introduction: If we would appreciate the power of this great master, we must acquaint ourselves with the age and time in which he lived. But we are not to regard his influence as living in his age and country alone, but rather to feel his power throughout all time and place, to feel him still alive in his great Hallelujah Chorus, as when he says he looked up and saw the Heavens open, and there stood the great God himself. He practically belongs to England, the practical sense of his music with its close adherence to the Bible, and its lofty imagination makes it strike the English people. Outside of England, he was mostly a curiosity, but to the English he is still with them their “meat and drink.” In the time of Handel, England was passing with rapid strides from a cold, cynical and intellectual world, to one awakening in life and thought. Underneath this strata of cold cynicism, was buried the emotional life of the nation, which was to be brought out by the great leaders of the time. The key note of conscience was struck by Whitfield and Wessley: and with it came a deeper compassion and feeling for mankind. The patriotic appeal is awakened by the heroic cry of Pitt, and the artistic sentiment is set forth by Handel.
Citation: Culp, Amanda. Handel's realm in music. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Music; Handel; Theses